Mechanical properties of symmetric and asymmetric DNA A-tracts: implications for looping and nucleosome positioning - Dršata, Tomáš; Špačková, Nada; Jurečka, Petr; Zgarbová, Marie; Šponer, Jiří; Lankaš, Filip (Nucleic acids research, 2014)
A-tracts are functionally important DNA sequences which induce helix bending and have peculiar structural properties. While A-tract structure has been qualitatively well characterized, their mechanical properties remain controversial. A-tracts appear structurally rigid and resist nucleosome formation, but seem flexible in DNA looping. In this work, we investigate mechanical properties of symmetric AnTn and asymmetric A2n tracts for n = 3, 4, 5 using two types of coarse-grained models. The first model represents DNA as an ensemble of interacting rigid bases with non-local quadratic deformation energy, the second one treats DNA as an anisotropically bendable and twistable elastic rod. Parameters for both models are inferred from microsecond long, atomic-resolution molecular dynamics simulations. We find that asymmetric A-tracts are more rigid than the control G/C-rich sequence in localized distortions relevant for nucleosome formation, but are more flexible in global bending and twisting relevant for looping. The symmetric tracts, in contrast, are more rigid than asymmetric tracts and the control, both locally and globally. Our results can reconcile the contradictory stiffness data on A-tracts and suggest symmetric A-tracts to be more efficient in nucleosome exclusion than the asymmetric ones. This would open a new possibility of gene expression manipulation using A-tracts.
Keywords: simulace molekulární dynamiky; biomechanika; Adenine; sekvence nukleotidů; Base Sequence; konformace nukleové kyseliny; Biomechanical Phenomena; Nucleosomes; adenin; entropie; Nucleic Acid Conformation; Poly A; nukleozomy; Molecular Dynamics Simulation; DNA; poly A; Entropy